Nature's complex emulsion: The fat globules of milk. (July 2017) - Singh, Harjinder; Gallier, Sophie
Abstract: The milk fat globule in milk represents a unique emulsion system designed by Nature to deliver energy, essential fatty acids and lipid-soluble nutrients to the neonate. The fat globules range from 0.1 to 15 μm in diameter and are stabilised by milk fat globule membrane (MFGM) which is composed of phospholipids, various glycoproteins, enzymes and cholesterol. Extensive knowledge on the intracellular origin, composition and structure of fat globules and MFGM has been accumulated over the last 30 years. Recently, it has been speculated that the MFGM has profound effects on the accessibility of the triglycerides for lipase-catalysed digestion. This has initiated a large number of studies on the digestion of milk fat globules in various dairy systems involving both in vitro and in vivo human digestion models. In addition, the identification of health-beneficial components of MFGM has led to increasing interest in developing MFGM as a food ingredient with unique functional properties and health benefits. This review focuses on recent knowledge on composition and structure of fat globules, the MFGM, and the behaviour of fat globules during gastro-intestinal digestion. MFGM ingredients and their applications are briefly discussed. Graphical abstract: Highlights: The milk fat globule in milk represents a unique emulsion system designed by Nature to provide nutrition to the neonate. The fat globules are stabilised by a complex milk fat globule membrane (MFGM) which has an intracellular origin. MFGM has profound effects on the stability of fat globules during processing and during digestion. MFGM is known to contain components that have unique functional properties and health benefits. Fat globules and MFGM show complex structural changes during gastro-intestinal digestion.